Mitigation techniques for mobile communication systems over fading channels - Yang, Yuntao (Nanyang Technological University, 2021)
In mobile communication systems, mobile devices need to transmit information over fading channels in the urban area. This project is aimed to use some popular techniques which can mitigate the fading effect. In this project, the original channel environment of the AWGN channel and Rayleigh fading channel has been shown by calculating the bit-error rate (BER) and by analyzing the variation of BER with the increase of the signal bit’ssignal-to-noise ratio (SNR) through theories and simulation. Diversity and combining techniques have been chosen as the mitigation techniques. The three popular methods of diversity and combining i.e., selection combining (SC), maximum ratio combining (MRC), and equal gain combining (EGC) were simulated. The BER performance results of the three methods over Rayleigh fading channels are compared with those obtained from the corresponding theories. And the improvement has been analyzed. Later the hybrid combining techniques have been shown in the intelligence improvement part. SC-MRC is a popular hybrid combining technique, to further reduce computation complexity, switch and examine combining and MRC (SEC-MRC) has been tested and simulated, the amount of reduction has been shown in the number of searching branches and the processing time between SC-MRC and SEC-MRC.